Generation of intermittent turbulent inflow and initial conditions based on wavelet construction method - Zhou, Long; Grilliat, Julien; Delgado, Antonio (ERCOFTAC Series, 2015)
UnivIS-Import:2018-02-22:Pub.2015.tech.ITC.stmmec.genera

On the preliminary design of axial fans: extending the validity of the flow assumptions over the whole hydraulic characteristic and improvement of modeling - Semel, Matthias; Grashof, Bettina; Grilliat, Julien; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2014)
UnivIS-Import:2015-07-08:Pub.2014.tech.ITC.stmmec.onthep

Preliminary design of axial fans at off-design-working points - Semel, Matthias; Grilliat, Julien; Delgado, Antonio (Proceedings of the ASME Turbo Expo, 2014)
An analytical formulation for axial fan performances at and off design point is proposed for an arbitrary work distribution. It is shown that the total pressure, total-to-static pressure and hydraulic efficiency characteristics can be described by means of hyperbola, straight lines and parabola. This formulation is applied to axial fans with free vortex work distributions, allowing a theoretical study onto the influence of the hub-to-tip ratio. Theoretical predictions are compared with numerical simulations. Good qualitative agreements are found. Conclusions onto the best practice guidelines for the design of axial fan according to a free vortex work distributions are presented.
UnivIS-Import:2018-02-22:Pub.2014.tech.ITC.stmmec.prelim

Towards multiple operating point axial fan design - Semel, Matthias; Haag, Viktor; Delgado, Antonio; Grilliat, Julien (ASME Turbo Expo 2015: Turbine Technical Conference and Exposition, 2015)
The dimensionless performances of an axial fan are derived analytically from an arbitrary work distribution. The formulation is illustrated using five different work distributions at a selected operating point and comparing the resulting hydraulic characteristics. A first validation of the formulation is brought by means of RANS and URANS of an axial fan with free vortex work distribution. It is shown that a single RANS prediction at the design point allows predicting the hydraulic characteristic up to 20% off the design flow rate with very good accuracy. Based on these results, a strategy for axial fan design at multiple operating points is propose
UnivIS-Import:2016-06-01:Pub.2015.tech.ITC.stmmec.toward